Pendidikan Karakter Kesadaran Kosmolgi dan Ekologi di Pesantren - Evita Nur Apriliana; Mahfud Junaedi (Faculty of Education and Teacher Training, Institut Agama Islam Negeri Pekalongan, 2021)
This paper aims to formulate a model of character education in shaping students' awareness about the balance of cosmology and ecological continuity based on its implementation at As Suffah Institute Rembang. The research method used is a qualitative case study. The data was obtained from in-depth interviews, participant observations, and related reference studies. The collected data was analyzed using Miles and Huberman's interactive analysis model. The result of this study is As-Shuffah Institute developed a character education model based on the concept of Islamic Cosmology reflected from Suluk Syahadatain Sheikh Achmad Mutammakin and practical experience of KH. Ubaidillah Achmad in the assistance of the community Tolak Semen Kendeng. Character education steps used include four strategies, namely Uswah ḥasanah, the study of the yellow book riyaḍah, and Sufistic counseling. Therefore, students can be aware of the central identity in religion, such as how much monotheism and faith can produce the broadest possible benefit for humanity (the gift of the universe).